BMSC Transplantation Aggravates Inflammation, Oxidative Stress, and Fibrosis and Impairs Skeletal Muscle Regeneration - Liu, Xiaoguang; Zheng, Lifang; Zhou, Yongzhan; Chen, Yingjie; Chen, Peijie; Xiao, Weihua (Frontiers in Physiology, 2019)
Skeletal muscle contusion is one of the most common muscle injuries in sports medicine and traumatology. Bone marrow mesenchymal stem cell (BMSC) transplantation has been proposed as a promising strategy to promote skeletal muscle regeneration. However, the roles and underlying mechanisms of BMSCs in the regulation of skeletal muscle regeneration are still not completely clear. Here, we investigated the role of BMSC transplantation after muscle contusion. BMSCs were immediately transplanted into gastrocnemius muscles (GMs) following direct contusion. Comprehensive morphological and genetic analyses were performed after BMSC transplantation. BMSC transplantation exacerbated muscle fibrosis and inflammation, as evidenced by increased leukocyte and macrophage infiltration, increased inflammatory cytokines and chemokines, and increased matrix metalloproteinases. BMSC transplantation also increased muscle oxidative stress. Overall, BMSC transplantation aggravated inflammation, oxidative stress and fibrosis and impaired skeletal muscle regeneration. These results, shed new light on the role of BMSCs in regenerative medicine and indicate that caution is needed in the application of BMSCs for muscle injury.